Estudio De La Motivación Y Satisfacción Del Profesorado Para El Desempeño Profesional En Benguela (Angola) - Chipuca, Lúcia Fernanda Dassala; Díaz, Inmaculada Aznar; Rodríguez-García, Antonio-Manuel (European Scientific Journal, ESJ, 2016)
There are a few researches about motivation and job satisfaction, but we found some studies about teacher motivation and their satisfaction in their workplace. In Angola’s context, this topic emerges as a new field to research inside the school organization and management area, understanding this as body of knowledge and actions among people who converge on shared values and practices which are manifested through work. This papper deals with the study of teacher’s motivation and satisfaction for their professional performance in Benguela (Angola). Through it, we try to describe how the motivation and satisfaction can influence on the professional development of teachers who work in Secondary Education in Benguela. It is performed used a quantitative research methodology. The total sample was composed by 367 teachers. The results shows a high leveles of dissatisfaction and low motivation by teachers in Benguela’s research context.